Early Weaning Inhibits Intestinal Stem Cell Expansion to Disrupt the Intestinal Integrity of Duroc Piglets via Regulating the Keap1/Nrf2 Signaling - Ying-Chao Qin; Cheng-Long Jin; Ting-Cai Hu; Jia-Yi Zhou; Xiao-Fan Wang; Xiu-Qi Wang; Xiang-Feng Kong; Hui-Chao Yan (MDPI AG, 2024)
There are different stress resistance among different breeds of pigs. Changes in intestinal stem cells (ISCs) are still unclear among various breeds of piglets after early weaning. In the current study, Taoyuan Black and Duroc piglets were slaughtered at 21 days of age (early weaning day) and 24 days of age (3 days after early weaning) for 10 piglets in each group. The results showed that the rate of ISC-driven epithelial renewal in local Taoyuan Black pigs hardly changed after weaning for 3 days. However, weaning stress significantly reduced the weight of the duodenum and jejunum in Duroc piglets. Meanwhile, the jejunal villus height, tight junction-related proteins (ZO-1, Occludin, and Claudin1), as well as the trans-epithelial electrical resistance (TEER) values, were down-regulated after weaning for 3 days in Duroc piglets. Moreover, compared with Unweaned Duroc piglets, the numbers of Olfm4+ ISC cells, PCNA+ mitotic cells, SOX9+ secretory progenitor cells, and Villin+ absorptive cells in the jejunum were reduced significantly 3 days after weaning. And ex vivo jejunal crypt-derived organoids exhibited growth disadvantages in weaned Duroc piglets. Notably, the Keap1/Nrf2 signaling activities and the expression of HO-1 were significantly depressed in weaned Duroc piglets compared to Unweaned Duroc piglets. Thus, we can conclude that ISCs of Duroc piglets were more sensitive to weaning stress injury than Taoyuan Black piglets, and Keap1/Nrf2 signaling is involved in this process.